Regulation of Initiation of S Phase, Replication Checkpoint Signaling, and Maintenance of Mitotic Chromosome Structures during S Phase by Hsk1 Kinase in the Fission Yeast - Takeda, Tadayuki (The American Society for Cell Biology, 2001)
Hsk1, Saccharomyces cerevisiae Cdc7-related kinase in Shizosaccharomyces pombe, is required for G1/S transition and its kinase activity is controlled by the regulatory subunit Dfp1/Him1. Analyses of a newly isolated temperature-sensitive mutant, hsk1-89, reveal that Hsk1 plays crucial roles in DNA replication checkpoint signaling and maintenance of proper chromatin structures during mitotic S phase through regulating the functions of Rad3 (ATM)-Cds1 and Rad21 (cohesin), respectively, in addition to expected essential roles for initiation of mitotic DNA replication through phosphorylating Cdc19 (Mcm2). Checkpoint defect in hsk1-89 is indicated by accumulation of cut cells at 30°C. hsk1-89 displays synthetic lethality in combination with rad3 deletion, indicating that survival of hsk1-89 depends on Rad3-dependent checkpoint pathway. Cds1 kinase activation, which normally occurs in response to early S phase arrest by nucleotide deprivation, is largely impaired in hsk1-89. Furthermore, Cds1-dependent hyperphosphorylation of Dfp1 in response to hydroxyurea arrest is eliminated in hsk1-89, suggesting that sufficient activation of Hsk1-Dfp1 kinase is required for S phase entry and replication checkpoint signaling. hsk1-89 displays apparent defect in mitosis at 37°C leading to accumulation of cells with near 2C DNA content and with aberrant nuclear structures. These phenotypes are similar to those of rad21-K1 and are significantly enhanced in a hsk1-89 rad21-K1 double mutant. Consistent with essential roles of Rad21 as a component for the cohesin complex, sister chromatid cohesion is partially impaired in hsk1-89, suggesting a possibility that infrequent origin firing of the mutant may affect the cohesin functions during S phase.